RASHANATU AL-FIKR WA JAUDATU AL-MULAAHAZHAH LADAA MAJLIS AL-ULAMA' AL-INDUUNIISIY FI AL-IFTA' (Diraasah Tathbiiqiyah fi Qadhiyah al-Sharafi aw Tadawuli al-Umalaat) - Al-Amin, Zaid (Jurnal Al-Dustur, 2020)
Indonesian Ulema Council (MUI) is an independent institution comprises many Indonesian Muslim groups. The objectives of the Indonesian Ulema Council’s establishment are to strengthen religion in the way of Pancasila and maintain the harmony between the different religions in Indonesia. In order to achieve these goals, the seriousness of the Indonesian Ulema Council in performing their duties really required. And one of the most important tasks is to lead the community to practice Islamic law in their lives by producing fatwa on all issues related to the life of Indonesian society. It is hoped that these fatwa will solve the existing problems. Fatwa has a strong relationship with the carefulness and good observation. If this character is not owned by Mufti, then the result of his work must be questioned because they are important when producing fatwa.